Membuat Kemasan pada Usaha Beras Jagung di Desa Pabuaran, Kec. Bantar Bolang, Kab. Pemalang - Imam Gozali; Bambang Riyadi; Tasya Harsiami; Agus Wiyoso; Dwi Indah; Sisy Farah Adilah; Tanuri Tanuri; Rakiman Rakiman; RP Sigit Fiansyah; Susilo Susilo; Amalia Amalia; Syahrul Afifudin; Eko Supriyadi; Trista Rima Setya; Evi Nur Afidoh; Susi Afriyani; Lyan Audiah; Uci Tri Windarsih; Ilham Kurniawan; Ivan Kurniawan; Slamet Setia (Institut Teknologi dan Bisnis Semarang, 2025)
Community service activities (Abdimas) were carried out on July 30, 2023 with the topic of Making Packaging in the Business Jagung Rice in Pabuaran Village, Bantar Bolang District, Pemalang The background of the problems in this village is the lack of knowledge about techniques to market Corn Rice to a wider market. The purpose of this community service is to provide guidance on packaging techniques for homemade Jagung Rice products to become superior products of local wisdom of the Pabuaran community. The community service method is carried out with a participatory and educational approach, involving 10 residents, namely housewives. As a result of this service, the mothers can make better product packaging.